Relationship between serum hypoxia-inducible factor-1α and renal interstitial disease and its prognosis in IgA nephropathy - bo Li; Yan-fang Zhang; Xue Zhang; Han-fang Zhang; Ya-li Zheng (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To explore the relationship between serum hypoxia inducible factor-1α (HIF-1α) and renal interstitial lesions in primary IgA nephropathy (IgAN). Methods From August 2017 to August 2021, retrospective analysis was performed for 142 IgAN patients. The relevant clinical data were collected and serum HIF-1αlevel was detected. They were divided into two groups according to the severity of renal interstitial lesions. Proportion of renal tubulointerstitial lesions ≤25% was mild group while >25% severe group. Inter-group differences in various parameters were examined by multiple factors. Correlations between serum HIF-1α and risk factors of kidney disease progression were analyzed. ResultsNo statistically significant inter-group differences existed in gender, 24 h urine protein quantification, body mass index (BMI), serum albumin, low-density lipoprotein cholesterol, triglycerides or hypertension (P>0.05). As compared with mild group, age [(44.45±9.65) year vs (38.36±11.09) year], blood creatinine [(116.28±44.75) μmol/L vs (84.82±42.06) μmol/L], blood uric acid [(389.03±104.57) μmol/L vs (353.39±90.01) μmol/L], serum HIF-1α[(213.53±68.86) pg/L vs (141.13±60.61) pg/L] were higher (P<0.05) while hemoglobin [(124.11±28.24) g/L vs (134.18±22.07) g/L] was lower in severe group (P<0.05). Multivariate analysis revealed that serum HIF-1α and age were risk factors for renal interstitial disease. Serum HIF-1α was correlated positively with serum creatinine (r=0.465, P<0.05), 24 h urinary protein quantity (r=−0.420, P<0.05) and serum uric acid (r=−0.217, P<0.05) and negatively with hemoglobin (r=−0.284, P=0.003). ROC curve analysis of serum HIF-1α indicated that area under the curve was 0.760 (P<0.001), critical point of serum HIF-1α for diagnosing renal dysfunction was 201.50 pg/L and Uden index was 0.44. Conclusions Serum HIF-1α is associated with renal interstitial disease of IgAN and risk factors for IgAN progression. It is clinically feasible to track serum HIF-1α level to judge the prognosis of IgAN.